2003
DOI: 10.1159/000071827
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effects of Apolipoprotein E Polymorphism and Low-Density Lipoprotein Cholesterol on Cognitive Performance in Young Adults

Abstract: This study examined the relations of apolipoprotein E (ApoE) genotype and the low-density lipoprotein (LDL) cholesterol level to cognitive performance of 57 randomly selected healthy young adults. From the ongoing population-based study of Cardiovascular Risk in Young Finns, 25 men and 32 women were ApoE genotyped and participated in mental arithmetic and reaction time tasks. In contrast to findings obtained from studies with elderly subjects, ApoE4 polymorphism was associated with better cognitive performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…One reason for this may be variation in the statistical power for individual studies. Whereas some studies with large sample sizes, and therefore high statistical power, found no differences (e.g., Deary et al, 2003;Jorm et al, 2007;Taylor et al, in press), other studies with small sample sizes, and therefore lower statistical power, did find APOE ɛ4-related benefits (e.g., Acevedo et al, 2010;Marchant et al, 2010;Puttonen et al, 2003;Yu et al, 2000). Type I or II errors may explain some of the variation in findings, but generally studies with small Ns tend to either over-or underestimate effect sizes, whereas investigations with large Ns estimate effect sizes more accurately.…”
Section: It Is Clear That There Are Inconsistencies In Research Findimentioning
confidence: 99%
“…One reason for this may be variation in the statistical power for individual studies. Whereas some studies with large sample sizes, and therefore high statistical power, found no differences (e.g., Deary et al, 2003;Jorm et al, 2007;Taylor et al, in press), other studies with small sample sizes, and therefore lower statistical power, did find APOE ɛ4-related benefits (e.g., Acevedo et al, 2010;Marchant et al, 2010;Puttonen et al, 2003;Yu et al, 2000). Type I or II errors may explain some of the variation in findings, but generally studies with small Ns tend to either over-or underestimate effect sizes, whereas investigations with large Ns estimate effect sizes more accurately.…”
Section: It Is Clear That There Are Inconsistencies In Research Findimentioning
confidence: 99%
“…APOE-ε4 has been associated with higher rates of cognitive decline during normal aging [1,2] and with aggravating incidence in the context of several neurological disorders, including Alzheimer's disease. Intriguingly, several studies reported higher performances on global cognition, attention and episodic memory in young adult APOE-ε4 carriers compared to non-APOE-ε4 carriers [3][4][5][6]. Better cognitive functions with APOE-ε4 during the first decades of life followed by a negative influence after the fifth decade was interpreted as an antagonistic pleiotropic effect [6].…”
Section: Introductionmentioning
confidence: 99%
“…hypertension, high cholesterol and diabetes (Atzmon et al, 2002;Köhler et al, 2014;van Exel et al, 2002;Whitmer, Sidney, Selby, Johnston, & Yaffe, 2005), and interactions between vascular health, APOE and cognition are reported (de Frias, Schaie, & Willis, 2014;Peila et al, 2001;Puttonen, Elovainio, Kivimäki, Lehtimäki, & Keltikangas-Järvinen, 2003;Zade et al, 2010). Current behavioural research is neither considering the potential modifying effects of wider risk factors nor adequately controlling for them, though they undoubtedly contribute to the cognitive ageing trajectory (Herrup, 2010).…”
Section: Discussionmentioning
confidence: 99%